The Effect of the Concurrent Use of Angiotensin-Converting Enzyme Inhibitors or Receptor Blockers on Toxicity and Outcomes in Patients Treated with Radiotherapy: A Systematic Review and Meta-Analysis - Wan-Chuen Liao; Hala Shokr; Corinne Faivre-Finn; Clare Dempsey; Kaye Janine Williams; Li-Chia Chen (Pharmaceuticals)
Background/Objectives: ACEIs protect against radiation pneumonitis by reducing angiotensin II production, oxidative stress, and inflammation. This study highlights the significance of concurrent angiotensin-converting enzyme inhibitor (ACEI) or angiotensin receptor blocker (ARB) use in radiotherapy by evaluating its impact on radiotherapy-related side effects and survival outcomes, addressing the gap in existing research and providing insights to guide clinical practice in oncology. Methods: The literature was retrieved from the MEDLINE, EMBASE, Web of Science, and Scopus databases from January 2000 to October 2024. Studies on adults (≥18 years) with histologically confirmed cancer, receiving ACEIs or ARBs during radiotherapy, were included. Radiotherapy-related side effects and clinical outcomes were analysed using odds ratios (ORs) and 95% confidence intervals (95%CIs), comparing ACEI/ARB users to non-users. Differences in the median survival time, recurrence, and death rates were also calculated. Results: Sixteen studies (14 cohort studies and two randomised trials) were included. ACEI users exhibited a 50% reduction in the risk of ≥grade 2 radiation pneumonitis (OR: 0.50, 95%CI: 0.32–0.77) in lung cancer and significant reductions in the odds of proctitis (80%, OR: 0.20, 95%CI: 0.12–0.33), haematuria (75%, OR: 0.25, 95%CI: 0.16–0.41), and rectal bleeding (61%, OR: 0.39, 95%CI: 0.30–0.51) in prostate cancer. ACEI/ARB users showed reduced symptomatic radiation necrosis in brain metastases and better 6-month functional independence in supratentorial glioblastoma. Among six studies reporting survival, ACEI/ARB users had longer median survival in early-stage non-small-cell lung cancer and glioblastoma but shorter survival in small cell lung cancer and brain metastases. ARB users had inconsistent survival rates for lung cancer. The varying survival outcomes suggest that ACEIs/ARBs have different effects depending on the cancer type and stage, potentially influenced by cancer-specific factors, treatment protocols, or disease progression. Conclusions: ACEI use is associated with a reduction in radiation pneumonitis, but evidence for other radiotherapy-related toxicity and survival outcomes remains inconsistent across cancer types and severities. Further research should carefully control for confounders.